2016
DOI: 10.1007/s10661-016-5221-7
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of iodine in horse serum and its relationship with thyroxin concentration by geological difference

Abstract: In this study, iodine and thyroxin (T4) concentrations in the serum of 69 horses were investigated. Higher iodine concentrations were obtained from the horses housed in Chiba Prefecture. In contrast, T4 concentrations of horses at Shizuoka Prefecture were higher than those of horses at Chiba Prefecture. There was a significant correlation (r = 0.643, P < 0.001) between the iodine and T4 concentrations of horses at Saitama and Shizuoka prefectures. Although a significant correlation (r = 0.794, P < 0.001) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In our previous report [ 9 ], a higher mean serum iodine concentration was obtained in horses housed in the equestrian club in Chiba 1 (mean; 29.33 µ g/ l ). The mean serum iodine concentrations were found to be in the order of Chiba 1 >Chiba 2 =Chiba 3 =Yamanashi (newly added data in the present study, 23.80 ± 1.01 µ g/ l ) >Saitama =Shizuoka (including Shizuoka-a and Shizuoka-b in the present study) [ 9 ]. In contrast, this study showed an opposite trend for Br compared with that for iodine.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In our previous report [ 9 ], a higher mean serum iodine concentration was obtained in horses housed in the equestrian club in Chiba 1 (mean; 29.33 µ g/ l ). The mean serum iodine concentrations were found to be in the order of Chiba 1 >Chiba 2 =Chiba 3 =Yamanashi (newly added data in the present study, 23.80 ± 1.01 µ g/ l ) >Saitama =Shizuoka (including Shizuoka-a and Shizuoka-b in the present study) [ 9 ]. In contrast, this study showed an opposite trend for Br compared with that for iodine.…”
Section: Discussionmentioning
confidence: 88%
“…Shizuoka-a, horses pastured on green grass; Shizuoka-b, horses pastured in a sand paddock. The iodine concentrations in horses from Shizuoka, Chiba and Saitama were reported in another investigation [ 9 ]. ).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations